2020
DOI: 10.1111/jfpp.15069
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of amylose content, protein content, breakdown, and setback viscosity of Kadus rice and its flour by near‐infrared spectroscopy (NIRS) analysis

Abstract: One of the major problems in predicting the quality properties of rice is that conducting experiments can be highly expensive. Therefore, it may be necessary to explore prediction of quality properties through near‐infrared spectroscopy (NIRS). The present research was designed to survey the possibility of using NIRS to predict the Amylose Content (AC), Protein Content (PC), Breakdown Viscosity (BDV), and Setback Viscosity (SBV) of rice and its flour. R2cal to flour samples of AC, PC, BDV, and SBV produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…RPD value > 3 was observed for protein (3.46) and TDF (3.62) indicating that the model is providing results that are at par with wet chemical analysis. Similar RPD values of 3.76 and 2.42 were observed for PC and AC in Kadus rice from Iran ( 37 ), respectively.…”
Section: Resultssupporting
confidence: 69%
“…RPD value > 3 was observed for protein (3.46) and TDF (3.62) indicating that the model is providing results that are at par with wet chemical analysis. Similar RPD values of 3.76 and 2.42 were observed for PC and AC in Kadus rice from Iran ( 37 ), respectively.…”
Section: Resultssupporting
confidence: 69%
“…Near-infrared reflectance spectroscopy (NIRS) is one of the related research focuses currently, identified as a potential method to realize rapid prediction of the content of amylose and protein and other quality characters (Barnaby et al, 2020). Biancolillo et al (2019) and Burestan et al (2020) combined NIRS with soft independent modeling of class analogy (SIMCA) and partial least squares discriminant analysis (PLS-DA) for identifying Plodia interpunctella-infested rice. 95.6% of the edible and 97.5% of the contaminated specimens could be accurately identified through PLS-DA, and the prediction of insect erosion in stored rice could be realized by SIMCA.…”
Section: Nondestructive Detection Methodsmentioning
confidence: 99%
“…For that purpose, traditional laboratory methods (wet chemical analyses) for nutrient quantification are commonly used to quantify nutrient contents. However, these methods are slow and expensive and are, therefore, inadequate for this purpose [ 12 , 13 ] An alternative method for the rapid quantification of nutrient content in bio-based materials (manure and digestate) is spectroscopy in the near-infrared (NIR) wavelength range (780–2500 nm) and mid-infrared (MIR) range (2500–4000 nm) [ [14] , [15] , [16] , [17] , [18] , [19] ]. NIR spectroscopy is known for its weak absorption of overtone and combination bands, broadbands, and lack of distinct characteristics [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%